Peran Pergerakan Dakwah Masjid Baiturrahman Eramas 2000 di Media Sosial YouTube dalam Dakwah Islam di Era Digital - Kristian, Niko; Al Habib, M Fikri; Ilham B, M Arief; Hafiz, Abdul (LANCAH: Jurnal Inovasi dan Tren, 2024)
This research is to look at the role of the 2000 Baiturrahman Eramas Mosque Da'wah Movement on YouTube Social Media in Islamic Da'wah in the Digital Era. The research used a systematic literature review. The research results showed that the optimization of social media carried out by this mosque was by using YouTube, both live streaming and video reels. The optimization carried out above is already considered optimal, but it still needs to be developed with interesting content so that it always keeps up with the times.